Development of Problem-Based Student Worksheet Learning Media Using Geogebra to Improve Mathematical Reasoning Skills and Learning Independence - Puandi, Akhyar; Lubis, Asrin; Mulyono, Mulyono (UIN Sunan Gunung Djati Bandung, 2024)
This research examined the validity, practicality, and efficacy of LKPD problem-based learning media with geogebra in promoting students' mathematical thinking and learning independence. Research and development are employed. ADDIE is this study's development model. This study involved class XI students of one of the vocational schools in Deli Serdang Regency. The average score for LKPD learning media based on problem-based learning helped by geogebra was 4.75 with a valid category. LKPD media based on problem-based learning assisted by geogebra is practical because the average score of learning implementation was 87.22%, which is good, and positive student responses averaged 88.94%, which is very positive. The average classical completeness value of students was 93.75% with a very high category, the average learning objective achievement was 89.06%, and the average student responses were 88.94%, indicating that LKPD media based on problem-based learning assisted by geogebra is effective. The developed media can improve students' mathematical reasoning and learning independence, as shown by their N-gain values of 0.48 and 0.55, respectively.